A Role of Gamification in English Language Learning - M. Vanisree, (AG Volumes, 2024)
The term "educational gamification" refers to the incorporation of gaming mechanics and design principles into formal education. In today's world, where English is the language of communication in fields as diverse as business, sports, trade, and education, language study has assumed a central position. To make education more engaging for each individual student, several philosophies and methods have emerged. Learning a language using video games is an effective and novel approach that is rising in popularity. When it comes to learning a new language, gamification can be highly exciting and encouraging since there are so many obstacles to overcome, objectives to reach, and prizes to acquire.